Smoke Rings: Towards a Comprehensive Tobacco Free Policy for the Olympic Games. - Kelley Lee; Gary Fooks; Nathaniel Wander; Jennifer Fang (PLoS ONE, 2015)
The tobacco industry has long sought affiliation with major sporting events, including the Olympic Games, for marketing, advertising and promotion purposes. Since 1988, each Olympic Games has adopted a tobacco-free policy. Limited study of the effectiveness of the smoke-free policy has been undertaken to date, with none examining the tobacco industry's involvement with the Olympics or use of the Olympic brand.A comparison of the contents of Olympic tobacco-free policies from 1988 to 2014 was carried out by searching the websites of the IOC and host NOCs. The specific tobacco control measures adopted for each Games were compiled and compared with measures recommended by the WHO Tobacco Free Sports Initiative and Article 13 of the Framework Convention on Tobacco Control (FCTC). This was supported by semi-structured interviews of key informants involved with the adoption of tobacco-free policies for selected games. To understand the industry's interests in the Olympics, the Legacy Tobacco Documents Library (http://legacy.library.ucsf.edu) was systematically searched between June 2013 and August 2014. Company websites, secondary sources and media reports were also searched to triangulate the above data sources. This paper finds that, while most direct associations between tobacco and the Olympics have been prohibited since 1988, a variety of indirect associations undermine the Olympic tobacco-free policy. This is due to variation in the scope of tobacco-free policies, limited jurisdiction and continued efforts by the industry to be associated with Olympic ideals.The paper concludes that, compatible with the IOC's commitment to promoting healthy lifestyles, a comprehensive tobacco-free policy with standardized and binding measures should be adopted by the International Olympic Committee and all national Olympic committees.